Growth and feed utilization of Dow cichlid (Cichlasoma dovii) larvae fed Artemia nauplii - Günther Nonell, Jorge (Universidad de Costa Rica, 1995)
Growth and feed utilization of Dow cichlid larvae (Cichlasoma dovii) fed with Artemia nauplii during the [lISt 12 days are assessed and compared with the growth of the larvae of the jaguar cichlid (Cichlasoma managuense). Growth and feed utilization of both species are very similar, albeit slightly more advantageous in the Dow cichlid larvae. The larvae of C. dovii have however, a significantly greater initial weight (6.65 vs. 3.84 mg) and initial percentage dry weight (2LO vs. 16.7 %). The data are compared to those of Cichlasoma managuense with regard to their ecological status.